Plasmacytoid Dendritic Cells Are Largely Dispensable for the Pathogenesis of Experimental Inflammatory Bowel Disease - Sawai, Catherine M.; Serpas, Lee; Neto, Antonio Galvao; Jang, Geunhyo; Rashidfarrokhi, Ali; Kolbeck, Roland; Sanjuan, Miguel A.; Reizis, Boris; Sisirak, Vanja (Frontiers in Immunology, 2018)
Inflammatory bowel disease (IBD) is a chronic inflammatory condition caused by an aberrant immune response to microbial components of the gastrointestinal tract. Plasmacytoid dendritic cells (pDCs) are innate immune cells specialized in the production of type I interferons and were recently implicated in the pathogenesis of autoimmune disorders such as lupus and scleroderma. While pDCs were shown to infiltrate intestinal mucosa of IBD patients and proposed to participate in intestinal inflammation, their net contribution to the disease remains unclear. We addressed this question by targeting the pDC-specific transcription factor TCF4 (E2-2) in experimental IBD caused by deficiency of Wiskott-Aldrich syndrome protein (WASP) or of interleukin-10 (IL-10). Monoallelic Tcf4 deletion, which was previously shown to abrogate experimental lupus, did not affect autoimmunity manifestations or colitis in WASP-deficient animals. Furthermore, conditional biallelic Tcf4 targeting resulted in a near-complete pDC ablation, yet had no effect on the development of colitis in IL-10-deficient mice. Our results suggest that, in contrast to other inflammatory and autoimmune diseases, pDCs do not play a major role in the pathogenesis of intestinal inflammation during IBD.